Islamic Cultural History Learning Media Based on Cyberspace: An Analysis of Implementation, Challenges, and Opportunities in Madrasah Aliyah - Fitri Puan; Edi Purwanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to comprehensively analyze the implementation, challenges, and opportunities of using cyberspace-based learning media in the Islamic Cultural History (SKI) subject at Madrasah Aliyah in Medan. The research method used was qualitative, with data collected through in-depth interviews with 12 SKI teachers from 12 different Madrasah Aliyah. The results of the study indicate that, although conventional learning media, such as textbooks and whiteboards, are still widely used, there has been a significant increase in the utilization of cyberspace media, including PowerPoint, videos, and interactive applications like Quizizz and Wordwall. The main challenges faced by teachers include limited technological knowledge, resistance to change, time constraints, as well as inadequate technological infrastructure and internet access. Nevertheless, the integration of cyberspace media offers great opportunities to improve the quality of learning, develop 21st-century and Industrial Revolution 5.0 skills, and prepare students to face the digital era. The conclusion of this study emphasizes the need for a comprehensive strategy, such as teacher training and professional development, enhanced institutional support in providing technological infrastructure, and collaboration among teachers, schools, the government, and other stakeholders to optimize the integration of cyberspace media in SKI learning at Madrasah Aliyah